Suburbia as a Narrative Space in the Cinematic Universe of Douglas Sirk - Nieves Alberola Crespo; José Javier Juan Checa (Universitat Jaume I. Department of English Studies, 2021)
Douglas Sirk, now fully recognized as an influential filmmaker, was considered a successful but uninteresting director in the 1950s. His melodramas were considered bland and subsequently ignored because they focused on female-centric concerns. In the following decades, he started to be considered as an auteur that not only had an impeccable and vibrant mise-en-scène, but also a unique ability to deliver movies that might seem superficial on a surface level but were able to sneak in some subtle and revolutionary criticism about American society. The aim of this paper is to analyse the most rebellious and subversive aspects of Sirk's classic All that Heaven Allows (1955) from a gender perspective and how Todd Haynes's tribute Far from Heaven (2002) added new challenges by touching upon thorny subjects that already existed in Sirk's time but were deemed taboo for mass audiences.